HIV Tat-mediated induction of autophagy regulates the disruption of ZO-1 in brain endothelial cells. Issue 2 (2nd April 2020) - Liao, Ke; Niu, Fang; Hu, Guoku; Guo, Ming-Lei; Sil, Susmita; Buch, Shilpa
ABSTRACT: The blood-brain barrier (BBB) is a tight barrier that is critical for preventing the entry of pathogens and small molecules into the brain. HIV protein Tat (Tat) is known to disrupt the tight junctions of the BBB. Autophagy is an intracellular process that involves degradation and recycling of damaged organelles to the lysosome and has recently been implicated in the BBB disruption. The role of autophagy in Tat-mediated BBB disruption, however, remains elusive. Herein we hypothesized that Tat induces endothelial autophagy resulting in decreased expression of the tight junction protein ZO-1 leading to breach of the BBB. In this study, we demonstrated that exposure of human brain microvessel endothelial cells (HBMECs) to Tat resulted in induction of autophagy in a dose- and time-dependent manner, with upregulation of BECN1/Beclin 1, ATG5 and MAP1LC3B proteins and a concomitant downregulation of the tight junction protein ZO-1 ultimately leading to increased endothelial cell monolayer paracellular permeability in an in vitro BBB model. Pharmacological and genetic inhibition of autophagy resulted in the abrogation of Tat-mediated induction of MAP1LC3B with a concomitant restoration of tight junction proteins, thereby underscoring the role of autophagy in Tat-mediated breach of the BBB. Additionally, our data also demonstrated that Tat-mediated induction of autophagy involved PELI1/K63-linked ubiquitination of BECN1. Increased autophagy and decreased ZO-1 was further recapitulated in microvessels isolated from the brains of HIV Tg26 mice as well as the frontal cortex of HIV-infected autopsied brains. Overall, our findings identify autophagy as an important mechanism underlying Tat-mediated disruption of the BBB.